GROWTH INHIBITION OF MEDICALLY ANTIBIOTIC RESISTANT BACTERIA BY SPONGE-ASSOCIATED BACTERIA - Ocky Karna Radjasa (JOURNAL OF COASTAL DEVELOPMENT, 2008)
The improper and uncontrolled uses of antibiotics against pathogenic bacteria have resulted in theoccurrence of Multi Drugs Resistant bacteria. There is now an urgency to find alternative antibioticsto combat these bacteria. The metabolites from microorganisms are a rapidly growing field, due, atleast in part, to the suspicion that a number of metabolites obtained from algae and invertebrates maybe produced by associated microorganisms. Therefore, there is a shift in the search for secondarymetabolites from terrestrial to marine environment. Sponge-associated microorganisms are among ofthe most interesting and promising marine natural product sources, which produce polyketide and nonribosomal peptide products with various biological activities. In this study, marine bacteria wereisolated from sponge Haliclona sp. collected from North Java Sea, and were screened for antibacterialactivity against MDR strains. One out of 32 bacterial isolates were successfully screened and werefound to be active against MDR strains, strain Escherichia coli and strain Proteus sp., respectively.These active isolates were also capable of amplifying NRPS gene fragments necessary for thebiosynthesis of non ribosomal peptides. The identification results revealed that the active isolates areArthrobacter sp.